Chediak-Higashi Syndrome: A Case Report - Bilal, Hina (International Journal of Pathology, 2020)
Chediak-Higashi syndrome (CHS) is an uncommon autosomal recessive disorder. It is presented as partial hypopigmentation of eyes, hair and skin along with recurrent infections, bleeding diathesis and neurological defects. It is a rare disease so much so only five hundred cases have been reported worldwide so far. This disease has two phases accelerated and adolescent or adult phase. Such patients show large peroxidase positive granules in the cytoplasm of leukocytes. It should be differentiated from other causes of albinism presenting with immunodeficiency.